Skrining kognitif pada dewasa dan lansia di Kelurahan Gunung Ibul Kota Prabumulih - Nindela, Rini; Yusril, Yusril; Marisdina, Selly; Junaidi, Achmad; Okparasta, Andika; Anggraeni, Dya (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2023)
Development progress in various fields, including health, has an impact on increasing people's life expectancy and increasing the elderly population in Indonesia. The increase in the number of elderly people has resulted in an increase in the prevalence of non-communicable diseases (NCDs), including dementia. Dementia decreases patient’s independency, until it eventually becomes a burden for the family and the state both in terms of economy and psychosocial. With early detection, people with dementia can get treatment earlier so that the progressivity of the disease can be inhibited. Community service activities have been carried out in the form of cognitive function screening with the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina) examination, which is followed by counseling and distribution of pamphlets about dementia, in Gunung Ibul Village, Prabumulih City, South Sumatra province. This activity was attended by 40 people, consisting of 5 (12.5%) men and 35 (87.5%) women with an average age of 60.68 ± 9.22 years. There were 29 (72.5%) adults and elderly people with decreased cognitive function (MoCA-Ina score less than 26). Memory and visuospatial/executive are the most affected cognitive domains. Early detection of dementia needs to be carried out periodically, especially in at-risk populations. Dementia education activities also need to be intensified to raise public awareness about dementia.